2015
DOI: 10.1007/s13199-015-0338-y
|View full text |Cite
|
Sign up to set email alerts
|

Increased trehalose biosynthesis improves Mesorhizobium ciceri growth and symbiosis establishment in saline conditions

Abstract: Cicer arietinum (chickpea) is a legume very sensitive to salinity, and so are most of its rhizobial symbionts belonging to the species Mesorhizobium ciceri. We observed that exogenous trehalose (i.e., added to the growth medium) can significantly improve growth of M. ciceri strain Rch125 under moderate salinity. In order to test if endogenous trehalose (i.e., synthesized by the cell) could also enhance salt tolerance, strain Rch125 was genetically modified with various trehalose biosynthesis genes from Sinorhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
(59 reference statements)
2
15
0
Order By: Relevance
“…Salinity is one of the most serious environmental stresses limiting the growth of rhizobia, which fix atmospheric N 2 and supply host plants with N [ 6 , 9 ]. Cumulative results suggest that rhizobia show different levels of tolerance to salt stresses [ 2 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Salinity is one of the most serious environmental stresses limiting the growth of rhizobia, which fix atmospheric N 2 and supply host plants with N [ 6 , 9 ]. Cumulative results suggest that rhizobia show different levels of tolerance to salt stresses [ 2 , 5 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of osmoprotective compounds by de novo biosynthesis in rhizobia is considered an effective strategy of adaptation by rhizobia to salt stress by protecting cells from desiccation and osmotic stress [ 6 , 11 , 12 ]. Furthermore, application of exogenous osmoprotective compounds increases the salt tolerance of rhizobial strains, such as Mesorhizobium sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High salt concentrations have shown to have negative effects on growth and distribution of Rhizobium sp. in soil (Jenkins et al, 1989) through limiting root infection via reducing the number of Rhizobial cells followed by inhibition of nodule growth and damaging the activity of nodules (Laranjo and Oliveira, 2011;Brígido et al, 2012;Moussaid et al, 2015). However, several studies have identified salt tolerant Rhizobia.…”
Section: Discussionmentioning
confidence: 99%